Transforming Research Evidence into Teaching Practices: Teacher Educators' Perspectives on Evidence-Based Teaching - Sinaga, Dolli; Sibarani, Berlin; Siregar, Masitowarni; Ariatna; Husein, Rahmad (English Lecturers and Teachers Association (ELTA), 2025)
This study investigates the perspectives of teacher educators at SMP Putri Cahaya Medan regarding the integration of evidence-based teaching (EBT) into their classroom practices. Amid growing emphasis on utilizing research to enhance education, the gap between educational theory and practical implementation remains a critical concern. Using a mixed-methods approach, including interviews, surveys, and classroom observations, this research explores teacher educators’ attitudes, challenges, and strategies related to EBT. Findings indicate that while educators generally value research-informed practices, they face significant barriers such as time constraints, limited access to research, and conflicts between personal teaching philosophies and empirical findings. However, factors such as institutional support, collaborative learning environments, and contextual adaptation of research findings were identified as key enablers. The study concludes that systemic support and professional development are essential to empower teacher educators in effectively translating research evidence into meaningful teaching practices, thereby bridging the gap between research and classroom application.